Computer-Aided Design, Synthesis, and Antiviral Evaluation of Novel Acrylamides as Potential Inhibitors of E3-E2-E1 Glycoproteins Complex from Chikungunya Virus - Gabriel Felipe Silva Passos; Matheus Gabriel Moura Gomes; Thiago Mendonça de Aquino; João Xavier de Araújo-Júnior; Stephannie Janaina Maia de Souza; João Pedro Monteiro Cavalcante; Elane Conceição dos Santos; Ênio José Bassi; Edeildo Ferreira da Silva-Júnior (Pharmaceuticals, 2020)
Chikungunya virus (CHIKV) causes an infectious disease characterized by inflammation and pain of the musculoskeletal tissues accompanied by swelling in the joints and cartilage damage. Currently, there are no licensed vaccines or chemotherapeutic agents to prevent or treat CHIKV infections. In this context, our research aimed to explore the potential in vitro anti-CHIKV activity of acrylamide derivatives. In silico methods were applied to 132 Michael’s acceptors toward the six most important biological targets from CHIKV. Subsequently, the ten most promising acrylamides were selected and synthesized. From the cytotoxicity MTT assay, we verified that LQM330, 334, and 336 demonstrate high cell viability at 40 µM. Moreover, these derivatives exhibited anti-CHIKV activities, highlighting the compound LQM334 which exhibited an inhibition value of 81%. Thus, docking simulations were performed to suggest a potential CHIKV-target for LQM334. It was observed that the LQM334 has a high affinity towards the E3-E2-E1 glycoproteins complex. Moreover, LQM334 reduced the percentage of CHIKV-positive cells from 74.07 to 0.88%, 48h post-treatment on intracellular flow cytometry staining. In conclusion, all virtual simulations corroborated with experimental results, and LQM334 could be used as a promising anti-CHIKV scaffold for designing new drugs in the future.